KADAR FERITIN SERUM DAN HEMOGLOBIN PADA WANITA PASANGAN PENGANTIN BARU DI BALI - Luh Seri Ani; Made Bakta; INT Suryadhi; IN Bagiada (Jurnal Gizi dan Pangan, 2010)
Serum ferritin and hemoglobin concentration were used to iron deficiency anemia (IDA) tests over population. The prevalence of IDA prevalence in pregnant women were 18% over the world, 37.5% in Asia, and 46.5% in Bali. The iron supplementation that was administrated during pregnancy did not clinically proven to solve the problems. It was predicted that the IDA was existing before pregnant. So, the body iron store must be prepare before pregnancy period. This research aimed to know the serum ferritin and hemoglobin concentration in the new married women in Bali. The design of this research was descriptive cross sectional study and conducted at 276 new married women by multistage sampling method. Every participant was interviewed for characteristic data and taken blood sample to evaluate serum ferritin and hemoglobin. Serum ferritin and hemoglobin were examined by Immulite 2000 Ferritin and Sysmex SF-3000 and the data were analyzed by descriptive analysis. The mean of serum ferritin and hemoglobin concentration are 29.41±20.36 µg/dl and 11.35±0.92 g/dl. The serum ferritin level proportions 20-29 µg/dl, less than 20 µg/dl, and ≥100 µg/dl are 145 (51.9%), 130 (47.1%), and 1(0.4%), eventually. The hemoglobin value <12 g/dl was found in 36.2% population and amount 63.8% population with hemoglobin value ≥12 g/dl. According on iron status, the proportion of anemia was23.6%, proportion of iron deficiency was19.2% and proportion of IDA was14.1%. Based on the result, ferritin in the new married women Bali was mostly low level but hemoglobin concentration was mostly normal. Although, they have problem in the proportion of iron deficiency, anemia and iron deficiency anemia, that were 19.2%, 23.6% and 14.1%, respectively.